A people's history of the American Revolution : how common people shaped the fight for independence - Raphael, Ray. (New York : Perennial, 2002)
Chronicles the events surrounding the American Revolution from the standpoints of its everyday participants, including women, Native Americans, African-Americans, loyalists, and pacifists.
Originally published: New York : The New Press, 2001.
Includes bibliographical references and index.
Library Journal
Publisher's Weekly
Wilson's Senior High School
Adult.
Keywords: United States -- History -- 1775-1783, Revolution; United States -- History -- 1775-1783, Revolution -- Personal narratives; United States -- History -- 1775-1783, Revolution -- Social aspects; United States -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Personal narratives; United States -- History -- Revolution, 1775-1783 -- Social aspects